Geological Mapping and Rover Mobility Planning Integration: A Case Study for Zhurong Rover’s Landing Area - Haoli Ding; Enhui Zou; Lihui Lian; Wenzhen Ma; Yantong Huang; Teng Hu (Remote Sensing, 2025)
This study conducted a comprehensive geological background investigation of the Zhurong rover’s landing area in Utopia Planitia using 3.5 m/pixel DEM and 0.7 m/pixel DOM data and completed the compilation of a 1:250,000-scale geological map. A total of 17 geological structures were systematically identified within the landing area. Additionally, focusing on scientific questions regarding the evolution of troughs, cone units, and mesas, we theoretically designed an exploration route considering slope constraints by taking the Zhurong rover route design as a case study. This route, a conceptual design, starts from the hibernation location of the Zhurong rover and has a total length of 126 km. It can provide a reference for advancing detection strategies for volatile components (e.g., water and ice) and contribute to the design of the Tianwen-3 exploration route. Ultimately, this study aims to establish a general guideline for integrating geological mapping with rover mobility planning in future extraterrestrial exploration missions.